Leaders in solving problems peacefully in the Muang District Pattani Province - Daraman, Hassan (Al-HIKMAH Journal, 2024)
Leaders in solving problems peacefully in the Muang District Pattani Province as a whole found to be at a high level with the aspect of inspiration have the highest average and the issue of taking into account the individuality It has the lowest mean considering each aspect. The results can be summarized as follows: 1.1 In terms of ideological influence, it was found that the overall level was at a moderate level. with leaders showing their friendliness, showing kindness and friendliness to the people have the highest average And the leader clause clearly states the purpose and goals of the work. have the lowest average 1.2 In terms of inspiration, it was found that the overall level was at a moderate level. The leadership can motivate the subordinates to feel that the work they do is important and proud. They have the highest average and the leader assigns tasks based on individual abilities and aptitudes. have the lowest average 1.3 In terms of stimulating the use of intelligence, it was found that the overall level was at a moderate level. There is a leadership message encouraging subordinates and the public to express their opinions. and express ideas have the highest average and leaders suggesting information and alternative solutions with leaders encouraging and encouraging new experimental initiatives It is recommended when such operations are found to be faulty. have the lowest average 1.4 In regard to individuality, it was found that the overall level was at a moderate level. with leadership thinking and looking for mistakes before giving operational feedback. have the highest average and the leader to give advice, advice and assistance to the people as appropriate when there is a problem have the lowest average Administration of educational institutions, administrative administration according to the principles of good governance In the area of ​​Mueang District, Pattani Province, overall, it was found that the respondents have opinions on the administration of governance in accordance with the principles of good governance moderate with the aspect of administration in accordance with the principle of responsibility have the highest average and administration in accordance with the rule of law have the lowest average when considering each aspect can be summarized as follows: 2.1 In terms of administration according to the rule of law, it was found that the overall level was at a moderate level. with the leadership to manage the affairs with regard to justice to the people have the highest average and the leader to use his powers in administration with fairness and without discrimination have the lowest average 2.2 In terms of administration according to moral principles, it was found that the overall level was at a moderate level. There is an ethical leader in management. have the highest average And the leadership has morals in the administration. have the lowest average 2.3 In terms of administration according to the principle of transparency, it was found that the overall level was at a moderate level. The leaders have formulated strategic plans for proper and systematic budget management. have the highest average And the leader has the necessary and reliable information disclosure. for the public to be informed regularly have the lowest average 2.4 In terms of administrative administration according to the principle of participation, it was found that the overall picture was at a moderate level. There are leaders giving opportunities for people to participate in solving problems. have the highest average And the leader has given the opportunity for people to participate in formulating policies, implementing development plans. have the lowest average 2.5 In terms of administration according to the principle of responsibility, it was found that the overall picture was at a high level. The leadership is responsible for the results of the performance. have the highest average And the leaders are responsible for the consequences of their own decisions. have the lowest average 2.6 In terms of administration according to the principle of value for money, it was found that the overall picture was at a moderate level. There is a leader to manage the work to achieve the objectives and goals of the plan. according to the budget to carry out have the highest average And the leader has a pure assessment of the performance of his subordinates. have the lowest average